1991
DOI: 10.1227/00006123-199105000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Postoperative Residual Tumor in Ependymoma

Abstract: Between 1970 and 1989, 29 patients with intracranial ependymomas were evaluated and treated at the Children's Hospital in Boston. With a median follow-up of 82 months, the actuarial survival rates at 5 and 10 years were 61 ± 10% and 46 ± 12%, respectively. Anaplastic histological findings were uncommon (2 of 29). Initial postoperative radiotherapy was given to 25 patients, with a median tumor dose of 5360 cGy. With a median time to recurrence of 22 months, local failure (within 2 cm of original enhancing mass)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
4

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(48 citation statements)
references
References 0 publications
2
41
1
4
Order By: Relevance
“…5,9,12,18,19,34 For this analysis, confounding factors included the unreliability of surgical assessment of the degree of ablation 35 and differences in the composition of compared groups with respect to age, performance status, and tumor grade, site, and size. In the current series, as in previous studies, 15,16 no statistically significant difference in overall survival was observed on univariate or multivariate analysis.…”
Section: Prognostic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,9,12,18,19,34 For this analysis, confounding factors included the unreliability of surgical assessment of the degree of ablation 35 and differences in the composition of compared groups with respect to age, performance status, and tumor grade, site, and size. In the current series, as in previous studies, 15,16 no statistically significant difference in overall survival was observed on univariate or multivariate analysis.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…18 Nonetheless, the role of RT in treating Grade 2 ependymoma is controversial. In fact, the impact of RT on survival is not clearly supported by consistent statistical data, as no randomized trial has been conducted and retrospective studies have been uncontrolled or involved comparisons with historical controls, 20,29,35 while data on survival after surgery alone are severely limited in modern series.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors have been reported to influence prognosis, though clinical research in this area has produced many conflicting results. However, gross surgical resection and the use of radiotherapy have been consistently associated with enhanced event-free and overall survival (Nazar et al, 1990;Sutton et al, 1990;Healey et al, 1991;Vanuytsel et al, 1992;Ferrante et al, 1994;Pollack et al, 1995;Bouffet et al, 1998;Robertson et al, 1998;Horn et al, 1999;Grill et al, 2001). Histological features of anaplasia, such as mitoses, microvascular proliferation and necrosis, serve as indicators of biological behaviour in other gliomas, including diffuse astrocytic tumours and oligodendrogliomas (Cohadon et al, 1985;Burger and Green, 1987;Ellison, 1998).…”
mentioning
confidence: 99%
“…About fifty percent (50%) occur before five years of age. Two-thirds of ependymomas are located infratentorially 2,3,4,5,6 . The optimal management of fourth ventricular ependymomas remains controversial 7 .…”
Section: Dicussionmentioning
confidence: 99%